The Power Of Perception: How Brand Gestalt Influences Revisit Intention - Toetik Wulyatiningsih; Deske W. Mandagi (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to investigate the impacts of 4S brand gestalt dimensions, namely story, sensescape, servicescape, and stakeholder, on tourists' intention to revisit a destination. The data was collected through a survey-based approach from 357 visitors of North Sulawesi, Indonesia. The results obtained from the application of Structural Equation Modeling (SEM) analysis indicate that all four dimensions of brand gestalt, including story, sensescape, servicescape, and stakeholder are significant predictor of the tourists' intention to revisit the destination. Moreover, sensescape emerges as the most prominent determinant of revisit intention. This study proposes theoretical and managerial implications based on the obtained findings. Keywords- Brand gestalt, story, sensescape, servicescape, stakeholder revisit intention